Effect of surface treatments on the bond strength of resin-repaired resin matrix CAD-CAM ceramic: A scoping review - Albergardi, Ana Beatriz de Souza [UNESP]; Limírio, João Pedro Justino de Oliveira [UNESP]; Gomes, Jéssica Marcela de Luna [UNESP]; Pesqueira, Aldiéris Alves [UNESP]; Pellizzer, Eduardo Piza [UNESP] (Elsevier, 2025)
Objective: To evaluate the existing evidence on surface treatment techniques employed in the repair of resin matrix CAD-CAM ceramics and their effects on short- and long-term bond strength. Methodology: This scoping review was conducted following the PRISMA-ScR guidelines for scoping reviews and was registered on the Open Science Framework platform. Based on the PCC concept, where P: Resin matrix CAD-CAM ceramic blocks for CAD-CAM, C: Bond strength, and C: Surface treatments, a search was conducted in the PubMed, Embase, Web of Science, Scopus, and Lilacs (grey literature) databases until October 2024, with no language or date restrictions. Results: In vitro studies comparing mechanical and/or chemical surface treatments on the bond strength of resin composite repairs were included. A total of 47 studies were included in the qualitative analysis, of which 45 used both mechanical and chemical treatments, and 29 used chemical treatments alone. Conclusion: The combination of chemical and mechanical treatments is the appropriate option. Alumina blasting and silica coating are the most commonly used mechanical surface treatments, either alone or in conjunction with chemical treatments. Laser irradiation may serve as an alternative to conventional treatments. Clinical significance: The studies revealed variability among protocols for repairing resin matrix CAD-CAM ceramics, with the combined use of chemical and mechanical treatments being the most effective approach.
Keywords: CAD-CAM; Flexural strength